Pola Operasi Waduk Wonogiri Setelah Pembangunan Pintu Pelimpah Baru Untuk Pengendalian Banjir - Wijayanti, Paska; Istiarto, Istiarto; Jayadi, Rachmad (Department of Civil Engineering, Diponegoro University, 2021)
Wonogiri reservoir in upstream Bengawan Solo experienced sedimentation problems that endanger its operation. Much of sediments come from Keduang watershed. To overcome this problem, closure dike was constructed to localize the sediment from Keduang watershed. The dike divides the reservoir into main and sediment storage reservoirs, each has its spillway. This paper presents results of the study on Wonogiri Reservoir operation during flood period after dike construction. The study followed a two-step calculation. It updated the design flood by employing rainfall data frequency analysis and Collins unit hydrograph. Flood routing was subsequently done by applying level pool method. Two conditions were considered, namely existing condition whose initial water level was +135.3 meters and new condition whose initial water level was +136.3 meters. The study reveals an increase of the flood discharge to Wonogiri reservoir by 7.7% and 3.6% for the 60 year and 500 year floods, respectively, as compared to the previous study of Pradipta (2014). The study shows that Wonogiri reservoir is prone to overtopping under 500 year flood. It is recommended to lower the control water level of the new spillway.